NASKAH AL-MU’ASHARAH SEBAGAI MEDIA PENGENALAN KISAH-KISAH INSPIRATIF ISLAMI KEPADA GENERASI MILLENIAL - Yulfira Riza (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
One of Shekh Abdul Latif Shakur’s, from Balai Gurah Agam, work is al-Mu’asharah. It have been inspired by various Arabic references which were than rewrite into Malay Language, the common language of general Minagkabau society. This paper aims to reveal the relation of it with other text which related to. Based on intertext method, it was found that some of the heroic stories in al-Mu’asharah came from Arabic manuscript. Hashiyah al-Bujairimi ‘ala Sharh Manhaj al-Tullab of Sulaiman al-Bujairimi; Tuhfah al-‘Arusin fi Sadat al-Zawjin of Muhammad Amin al-Danawiy and Tafsir al-Quran al-‘Azhim of Ibnu Kathir inspire Shakur to write some stories and Amirul Mukminin’s story when he become Khalifah. Stories of Abu al-Dard?’ and Salman al-Farisi sourced from al-Muhdhab of Abu Ishaq al Shirazy. In Addition, it was also found that al-Qur’an and Tafsir al Qur’an al ‘Azhim are Shakur’s references to write stories about Asiah, Paraoh’s wife, and Musa who was married to the daughter of Shu’ib in Madyan. The stories are retold by Shakur in a simple language hoping that all Islamic generations will read it. Rewriting these stories are expected to be an Islamic references for the millenial generation whose their reading resourses have been dominated by non-Islamic figures.